2007
DOI: 10.1007/bf03194235
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and reproductive patterns of wild European polecatsMustela putorius in Denmark

Abstract: Accurate information about age structure, survival and reproductive biology is a prerequisite for understanding various aspects of a species' population ecology and life history biology (Stearns 1992), for constructing models of population dynamics (Vandermeer and Goldberg 2003) and for developing management strategies (Caughley 1977). Examinations of carcasses of harvested or accidentally killed individuals are a widely used method to establish life tables as well as to ascertain reproductive information such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In the Mackenzie Basin, survival of juveniles varied from 19% to 100% in the 4 months after emergence from the natal den, decreasing to 0–60% by the end of the first winter, depending inversely on ferret density (Byrom 2002 ). Annual survival rates of 15–65% have been reported for feral ferrets in New Zealand (Norbury and Heyward 1997 ; Morley 2002 ; Byrom et al 2008 ), similar to reported rates of 32–67% for the polecat in Europe (Kristiansen et al 2007 ). Due to the high annual mortality rate among ferrets, they are regarded as less likely to contribute to risk of TB persistence than longer-lived wildlife hosts of TB in New Zealand, such as wild deer (Barron et al 2013 ; Nugent et al 2015b ).…”
Section: The Epidemiology Of Tb and Its Relationship To Ferret Ecologsupporting
confidence: 68%
“…In the Mackenzie Basin, survival of juveniles varied from 19% to 100% in the 4 months after emergence from the natal den, decreasing to 0–60% by the end of the first winter, depending inversely on ferret density (Byrom 2002 ). Annual survival rates of 15–65% have been reported for feral ferrets in New Zealand (Norbury and Heyward 1997 ; Morley 2002 ; Byrom et al 2008 ), similar to reported rates of 32–67% for the polecat in Europe (Kristiansen et al 2007 ). Due to the high annual mortality rate among ferrets, they are regarded as less likely to contribute to risk of TB persistence than longer-lived wildlife hosts of TB in New Zealand, such as wild deer (Barron et al 2013 ; Nugent et al 2015b ).…”
Section: The Epidemiology Of Tb and Its Relationship To Ferret Ecologsupporting
confidence: 68%
“…In other geographic regions, where the ecology of the polecat is better known, road fatalities are also a major cause of polecat deaths (Blandford 1987;Birks 1997;Mitchell-Jones et al 1999;Lodé 2003;Kristiansen et al 2007). Despite these Wndings and that road-kills seem to be concentrated along certain stretches of road (Blandford 1987), no studies have analysed habitat and road-related variables at speciWc locations where road-kills occur.…”
Section: Introductionmentioning
confidence: 95%
“…Since uteri from all categories of females are readily obtained from hunters and trappers; placental scars are often the best source of information on fox reproduction. Counting of placental scars and embryos in the uterus has been widely used in a number of mammalian species, including several rodents (Martin et al 1976), lagomorphs (Bray et al 2003) and carnivores (Lindström 1994;Helle and Kauhala 1995;Mowat et al 1996;Asano et al 2003;Elmeros et al 2003;Elmeros and Hammershøj 2006;Kristiansen et al 2007) to estimate female fecundity in free-ranging populations. Indeed, in mammals with a zonary endoepitheliochorial or discoid hemochorial type of placenta, a distinct implantation site is formed for each foetus in the uterus.…”
Section: Introductionmentioning
confidence: 99%